2016
DOI: 10.7196/ajhpe.2016.v8i1.758
|View full text |Cite
|
Sign up to set email alerts
|

Feedback as a means to improve clinical competencies: Consultants’ perceptions of the quality of feedback given to registrars

Abstract: Background. Effective supervision by consultants in postgraduate medical education involves the process of feedback. Giving feedback may be challenging for consultants who have no formal training in this process, which may be further compounded in heterogeneous diverse settings. Objective. To explore consultants' perceptions of feedback to registrars in a multicultural, multilingual diverse academic hospital setting. Methods. Thirty-seven consultants consented to completing a questionnaire on what, when, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This belief was borne out by the findings that only just over a third of the consultants communicated in advance the desired standards of performance to be obtained and only about 40% gave feedback always or often (Bagwandeen and Singaram 2016a). More importantly, these studies found that the registrars believed that the feedback provided was influenced by their race, gender and ethnicity.…”
mentioning
confidence: 92%
“…This belief was borne out by the findings that only just over a third of the consultants communicated in advance the desired standards of performance to be obtained and only about 40% gave feedback always or often (Bagwandeen and Singaram 2016a). More importantly, these studies found that the registrars believed that the feedback provided was influenced by their race, gender and ethnicity.…”
mentioning
confidence: 92%
“…Implementing such initiatives with frequent feedback sessions based on pre-determined objectives and a plan for improvement may promote and enhance the feedback culture within anaesthesiology. 1,14,15,25 Our study found that, whilst all consultants provide feedback, very few acknowledged the continuous ongoing nature of feedback and many were unsure if the time spent with the trainee was adequate. Trainers reported often working with a different trainee in theatre and that trainees were exposed to a pool of consultants rather than an individual.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to previous studies, we found that almost half of the trainers admitted to having difficulty giving negative feedback, as they felt the trainee may react negatively. 14 This is a major barrier to feedback, which leads to missed opportunities for the trainee to recognise underperformance and improve. Unchecked, a trainee may pass through a specialty over-confident without realising their shortcomings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations